Quick method for identification of inoculation nodules, efficiency of N2 fixation and cross inoculation of tropical legumes - Stamford, Newton Pereira (Pesquisa Agropecuaria Brasileira, 2014)
Experiments using leonard jars, soil pots, and field experiments were conducted to observe cross-inoculation in some tropical legumes, the possibility of using black nodule-producing strains for identification of Rhizobium nodules and also the efficiency of such strains in nitrogen fixation. The tropical legumes used were: glycine (Neotonia wightii), lablab (Lablab purpureus), centro (Centrosema pubescens), tropical kudzu (Pueraria phaseoloides) and calopo (Calopogonium mucunoides), inoculated with black nodule-producing strains and normal strains. In cross-inoculation behavior certain host specificity was observed in centro. Lablab and calopo formed black nodules with all black nodule-producing strains, centro with C-102 and CM-7, and glycine produced no black nodules. Strains showed differences in nitrogen fixation efficiency and, in a general way, black nodule-producing strains showed highest efficiency in nitrogen fixation. Results indicated that the black nodule-producing strains may be used in Rhizobium strain identification.
Keywords: Rhizobium identification; black nodule strains; Centrosema pubescens; tropical kudzu